Experimental and Theoretical Investigation of Wave Forces on Rigid Vertical Cylinders - Kurian, V.J. (2014)
An experimental study has been carried out to investigate the hydrodynamic forces on rigid tubular cantilever cylinders with a freeend condition subjected to regular waves. This paper presents the preliminary results of wave tank model test conducted to determine the hydrodynamic forces on vertical rigid cylinders subjected to regular wave loadings. The paper emphasizes on comparison of experimental results with those determined numerically using Morison equation. The comparison of experimental results with the numerical estimations is necessary for accurate prediction of hydrodynamic coefficients. The experimental data are generated from wave tank model test with a scale factor of 1: 40. The cylinder diameters covered in this paper are 42 mm and 34 mm respectively. The findings presented in this paper are part of on-going experimental investigations intended to determine accurate inertia (Cm) and drag (Cd) coefficients. Generally, the experimental hydrodynamic forces are in good agreement with the theoretical values. The findings of this research can be used to determine accurate hydrodynamic coefficients for Malaysian offshore locations